Cervical spine evaluation and clearance in the intoxicated patient: A prospective Western Trauma Association Multi-Institutional Trial and Survey. Issue 6 (December 2017) - Martin, Matthew J.; Bush, Lisa D.; Inaba, Kenji; Byerly, Saskya; Schreiber, Martin; Peck, Kimberly A.; Barmparas, Galinos; Menaker, Jay; Hazelton, Joshua P.; Coimbra, Raul; Zielinski, Martin D.; Brown, Carlos V.R.; et al.
Abstract : BACKGROUND: Intoxication often prevents clinical clearance of the cervical spine (Csp) after trauma leading to prolonged immobilization even with a normal computed tomography (CT) scan. We evaluated the accuracy of CT at detecting clinically significant Csp injury, and surveyed participants on related opinions and practice. METHODS: A prospective multicenter study (2013–2015) at 17 centers. All adult blunt trauma patients underwent structured clinical examination and imaging including a Csp CT, with follow-up thru discharge. alcohol- and drug-intoxicated patients (TOX+) were identified by serum and/or urine testing. Primary outcomes included the incidence and type of Csp injuries, the accuracy of CT scan, and the impact of TOX+ on the time to Csp clearance. A 36-item survey querying local protocols, practices, and opinions in the TOX+ population was administered. RESULTS: Ten thousand one hundred ninety-one patients were prospectively enrolled and underwent CT Csp during the initial trauma evaluation. The majority were men (67%), had vehicular trauma or falls (83%), with mean age of 48 years, and mean Injury Severity Score (ISS) of 11. The overall incidence of Csp injury was 10.6%. TOX+ comprised 30% of the cohort (19% EtOH only, 6% drug only, and 5% both). TOX+ were significantly younger (41 years vs. 51 years; p < 0.01) but with similar mean Injury Severity Score (11) and Glasgow Coma Scale score (13). The TOX+ cohort had a lower incidence of Csp injury versus nonintoxicated (8.4% vs. 11.5%; p < 0.01). In the TOX+ group, CT had a sensitivity of 94%, specificity of 99.5%, and negative predictive value (NPV) of 99.5% for all Csp injuries. For clinically significant injuries, the NPV was 99.9%, and there were no unstable Csp injuries missed by CT (NPV, 100%). When CT Csp was negative, TOX+ led to longer immobilization versus sober patients (mean, 8 hours vs. 2 hours; p < 0.01), and prolonged immobilization (>12 hrs) in 25%. The survey showed marked variations in protocols, definitions, and Csp clearance practices among participating centers, although 100% indicated willingness to change practice based on these data. CONCLUSION: For intoxicated patients undergoing Csp imaging, CT scan was highly accurate and reliable for identifying clinically significant spine injuries, and had a 100% NPV for identifying unstable injuries. CT-based clearance in TOX+ patients appears safe and may avoid unnecessary prolonged immobilization. There was wide disparity in practices, definitions, and opinions among the participating centers. LEVEL OF EVIDENCE: Diagnostic tests or criteria, level II. Abstract : Supplemental digital content is available in the text.